Bentuk Lagu “Sendah Kerja Rani” - Erika Tri Yeni; Syahrul Suah Sinaga; Slamet Haryono (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Runggun Semarang Batak Karo Protestant Church (GBKP) celebrates kerja rani and song “Sendah Kerja Rani” is a Karo spiritual song found in the book kitab end-endwhich has cultural values, is still sung at GBKP Runggun Semarang.The purpose of writing this article is to analyze the form of the “Sendah Kerja Rani” song using a qualitative research method, a musicological approach, and an approach that involves reading problems in the scientific field of music, such as form and context. “Sendah Kerja Rani” song is a two-part song consisting of sentence A (a, a') and sentence B (b, y), there are three motifs in the “Sendah Kerja Rani” song namely literal repetition, repetition at sequence level, and interval reduction, then cadence